Cultural Intelligence and Employee Well-Being at Intercultural Environment; Intergovernmental and Nongovernmental Organizations (NGO & IGO) context. (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2016)
The aim of this study is to explore relationship between Cultural intelligence CQ and Employee well-being, using cultural intelligence and employee well-being questionnarie.The research survey sampling to target is Intergovernmental and Nongovernmental organizations (NGO & IGO) employees and expatries that operating in Gaziantep,Turkey.These kind of organizations has providing social,economic,logistics development for both public and private business sector even in developed country,also emergency natural disaster and humanatarian aid around the globe.That is obvious we can not ignore that contributions of their international and national staff experience from different nationalities.Main outcome of our researche, there is a significant positive correlation between motivational CQ and employee well-beign. You can find details on the results of research.Keywords; Intergovernmental and Nongovernmental Organizations ( IGO&NGO ), Cultural Intelligence ( CQ ),Employee Well-Being.